Balancing green and growth: do innovation and contribution drive sales and environmental performance? - Rana Yassir Hussain; Muhammad Adil; Geoffrey Norman Tumwine; Haroon Hussain; Hira Irshad (Discover Sustainability)
Abstract This study examines the impact of industrial innovations and contributions on the new products’ sales and environmental performance. The Present study adds to the prior knowledge by incorporating the environmental concerns emanating from the sales of new products. The past literature in this domain is scant, primarily concentrating on overall figures. The impact is analysed using the two-step system Generalised Method of Moments (GMM) regression approaches to analyse 30 provinces’ worth of combined data from Chinese firms from 2009 to 2020. The results show that foreign fund flows have a negative effect on new products’ sales and environmental performance. Besides, industrial innovation, measured through the effective number of patents, has a positive effect on the sales of new products but a negative impact on their environmental performance. Meanwhile, R&D expenditures positively affect sales and environmental performance of new products. Industrial expenditures positively affect new products’ sales and environmental performance by improving manufacturing processes and adopting eco-friendly technologies. The study proposes that policymakers implement policies related to green innovations, sustainable practices and eco-friendly technologies in industrial zones. Adopting efficient R&D strategies can lead to manufacturing products that meet market demands and create less harm to the environment.